Protection of Communal Copyrights through Sui Generis Law - Haryono Haryono (Budapest International Research and Critics University, 2022)
The purpose of this study is to find answers to why the value of local wisdom is the basis for building Copyright law and how the construction of Copyright law based on the value of local wisdom provides creative freedom and can improve people's welfare. The paradigm in this research is Legal Constructivism, with a socio-legal research approach. The social setting is the written batik community. Primary data was obtained by interview and observation, while secondary data was obtained by document study. Primary data were analyzed using the four-step model of Mathew B. Miles and A. Michel Huberman. Secondary data were analyzed using hermeneutics. The results of the study show that if copyright law is not based on local wisdom values, it has the consequence that copyright law does not work well, because the legal values do not match the values of local wisdom and are unable to protect communal copyrights. Society becomes ambiguous, and people are not prosperous because they do not have the freedom to be creative in their work. The values of local wisdom are the basis for building copyright law. The value of local wisdom can protect copyrighted works that are communal. Local wisdom can improve the welfare of the community. The ideal construction of copyright law reconstructs its structure, substance, and culture. The principles of supporting new copyrights are the principles of justice, economy, culture, social, communal ownership, availability of access, and an integrated strategy.